2022
DOI: 10.1002/jrs.6301
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration rate of the glycine‐MgSO4·5H2O complex and the stability of glycine expelled from the complex by in situ Raman spectroscopy under Mars‐relevant conditions

Abstract: In this work, we studied the dehydration process of the glycine‐MgSO4·5H2O complex under Mars‐relevant conditions (99% CO2 and 0.6% H2O under ultra violet (UV) irradiation exposure at 7‐mbar pressure and high vacuum conditions: 8 × 10−5 and 5 × 10−5 mbar) by in situ Raman spectroscopy inside a planetary atmosphere and surface chamber (PASC). This work provides quality Raman spectra taken under simulated planetary conditions (to be integrated in a database), as Raman spectroscopy forms part of the current and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A Martian-like CO 2 atmosphere was not introduced into the chamber to prevent absorption of UV by CO 2 and contamination from air. Previous studies have shown that a few mbars of CO 2 have no influence on the UV induced degradation of amino acids (ten Kate et al, 2006), nor on the UV induced dehydration of sulfates (Bonales et al, 2022). Of note, all the samples have been introduced into the Martian chamber and exposed to the pressure and temperature conditions of the experiments for 15 hours before being exposed to UV radiation.…”
Section: Selected Minerals and General Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…A Martian-like CO 2 atmosphere was not introduced into the chamber to prevent absorption of UV by CO 2 and contamination from air. Previous studies have shown that a few mbars of CO 2 have no influence on the UV induced degradation of amino acids (ten Kate et al, 2006), nor on the UV induced dehydration of sulfates (Bonales et al, 2022). Of note, all the samples have been introduced into the Martian chamber and exposed to the pressure and temperature conditions of the experiments for 15 hours before being exposed to UV radiation.…”
Section: Selected Minerals and General Strategymentioning
confidence: 99%
“…Of note, all initially hydrated starting materials do not show anymore Raman features attributed to hydration at the end of the present experiments. Yet, neither Morris and Lauer (1980) nor Yen et al (1999) observed UV photodehydration, but Bonales et al (2022) experimentally showed that exposure to UV enhances the kinetics of dehydration. Dehydration may be a direct consequence of the simulated Martian conditions.…”
Section: Impact Of Exposure To Uv Radiationmentioning
confidence: 99%
See 1 more Smart Citation